Review of Hypoparathyroidism - Abate, Ejigayehu G.; Clarke, Bart L. (Frontiers in Endocrinology, 2017)
Hypoparathyroidism is a rare endocrine disorder in which parathyroid hormone (PTH) production is abnormally low or absent, resulting in low serum calcium and increased serum phosphorus. The most common cause of hypoparathyroidism is parathyroid gland injury or inadvertent removal during thyroid surgery. Current treatments include supplementation with calcium and active vitamin D, with goal albumin-corrected serum calcium level in the low-normal range of 8-9mg/dl. Complications of the disease include renal dysfunction, nephrocalcinosis, kidney stones, extracellular calcifications of the basal ganglia, and posterior subcapsular cataracts, as well as low bone turnover and increased bone density. Until January 2015, hypoparathyroidism was the only classic endocrine disease without an available hormone replacement. Recombinant human PTH 1-84, full length parathyroid hormone, is now available for a selected group of patients with the disease who are not well controlled on the current standard therapy of calcium and active vitamin D. In addition, the role of PTH replacement on quality of life, intracerebral calcifications, cataracts, improving bone turnover, and reduction of renal complications of the disease remains to be further investigated.